EFFICACY OF TAX PAYERS’ PERCEPTION ON TAX COMPLIANCE LEVEL AMONG SMEs IN ILORIN METROPOLIS - Daud Omotosho Saheed; Yusuf Olamilekan Quadri; Majeed Ajibola Ibrahim; Ifedolapo Oluwasolape Omotosho (Malete Journal of Accounting and Finance)
Nigeria’s tax compliance rate is significantly low compared to other countries especially given the weak revenue administration capacity to deal with evasion and lack of data mainly around the informal sectors as tax payers do not trust the government to channel tax revenue for its intended purposes. Hence, this study sought to examine the efficacy of taxpayer’s perception on tax compliance level among the Small and Medium Enterprises in Ilorin metropolis of Kwara State.  A purposive sampling method was adopted to select the sample of respondents that serve as the fair representation of the population under study. A closed ended questionnaire was used for data collection while analyses was done through descriptive as well as inferential statistics with Statistical Package for the Social Science (SPSS). The formulated hypotheses were tested using regression and correlation analysis. The X-ray of the findings shows a positives statistically significant relationship between an efficient educational service provision and tax compliance level. Equally, a positive and statistically significant relationship also exists between health service provision and tax compliance level. The reported coefficient from the correlation result however revealed that there was no statistical significant relationship between the characteristics of taxpayer’s perception and tax compliance level among the population under study. The study recommends among many other that government should ensure an efficient utilization of tax revenue with a view of influencing the perception of taxpayer’s towards tax compliance level.